2018
DOI: 10.2174/1874325001812010075
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Ultrasonographic Evaluation for Malignancy of Soft-Tissue Sarcoma: A Retrospective Study

Abstract: Background:Ultrasonography is useful for distinguishing between benign and malignant soft-tissue tumors. However, no study has focused on its usefulness in the differential diagnosis between low-grade and high-grade soft-tissue sarcomas. We conducted a retrospective study to determine the usefulness of the parameters of ultrasonograph and to develop a practical scoring system for distinguishing between high-grade and low-grade sarcomas.Methods:Twenty-two cases of low-grade and 43 cases of high-grade malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Unplanned excisions performed in the other hospital caused tumor contamination, which created the need for a wider reexcision area to obtain a negative surgical margin. 11,21,22 Moreover, univariate analysis of this study showed that the group that needed reconstruction was significantly more likely to have distant metastasis. Some authors reported that larger tumor size was a poor prognostic factor for distant metastasis.…”
Section: Discussionmentioning
confidence: 61%
“…Unplanned excisions performed in the other hospital caused tumor contamination, which created the need for a wider reexcision area to obtain a negative surgical margin. 11,21,22 Moreover, univariate analysis of this study showed that the group that needed reconstruction was significantly more likely to have distant metastasis. Some authors reported that larger tumor size was a poor prognostic factor for distant metastasis.…”
Section: Discussionmentioning
confidence: 61%
“…Previous groups have reported that more than one‐third of patients with sarcomas who have undergone UE had the presence of “alarm” symptoms before the surgery which may have warranted referral or further diagnostic imaging before surgery . Further, radiographic appearance on ultrasound may demonstrate suspicious features even in small lesions, and core‐needle biopsy has been demonstrated to identify the grade and histological subtype of STS . In the present study, all patients were treated at tertiary or quaternary referral centers after UE with multidisciplinary specialists in the treatment of STS.…”
Section: Discussionmentioning
confidence: 83%
“…25 Further, radiographic appearance on ultrasound may demonstrate suspicious features even in small lesions, and core-needle biopsy has been demonstrated to identify the grade and histological subtype of STS. [26][27][28][29] In the present study, all patients were treated at tertiary or quaternary referral centers after UE with multidisciplinary specialists in the treatment of STS. This may partially account for the similar DSS and DMFS seen in our study cohorts, but also stresses the need for multimodality therapy in the treatment of STS.…”
Section: Discussionmentioning
confidence: 99%
“…Dedifferentiated liposarcomas account for almost 10% of the liposarcomas 22) , and this similar rate was noted between hypoechoic tumor in the previous study and the dedifferentiated liposarcoma supports this hypothesis. In another study, most well-differentiated liposarcomas did not show hypoechoic echogenicity 21) , and hypoechoic echogenicity could be the specific property of high-grade liposarcomas rather than low-grade liposarcomas. Echogenicity of liposarcoma should be determined by its pathological component, though there are no discussions explaining the echogenicity variation of liposarcomas in previous reports.…”
Section: Discussionmentioning
confidence: 89%
“…According to some reports, echogenicity is not a significant factor while estimating malignancy risk in sarcomas 18,19) . On the other hand, some studies showed that low echogenicity is a characteristic of malignancy risk in soft tissue tumors 20,21) . Liposarcomas can be classified into four types according to the World Health Organization: atypical lipomatous tumor/well-differentiated liposarcoma, myxoid liposarcoma, pleomorphic liposarcoma, and dedifferentiated liposarcoma 22) .…”
Section: Discussionmentioning
confidence: 99%